FORESIGHT AND DESIGN composing future places. - Childs, Mark C., 1959- ([S.l.] : ROUTLEDGE, 2022)
Every plan, pro-forma, design, building contract, and construction schedule is a proposal about future places. To help improve such proposals, Foresight and Design: Composing Future Places presents conceptual tools to inform design and outline the need for designers to rigorously think about potential futures. Our built compositions are constantly transforming due to continuing urbanization, demographic shifts, climate change, the evolution of virtual worlds, economic and health disparities, and other unforeseen trends. If we envision and plan for alternative futures, we are better able to purposefully respond. This book presents emerging practices of foresight, including signals of change, thick descriptions, pace layers, (re)framing, prototyping, scenarios, maps of change, storytelling, and world-building, to indicate how robust contemplation of multiple potential futures can help us compose places that are durable, resilient, and adaptable. Five brief case studies interspersed between the chapters serve as examples of practitioners exercising foresight through these practices. Contributions include a description of a regional design process in Afghanistan by Anthony Fettes of Sasaki Architects, and an exploration into the Indigenous Futurism model-making competition by Anjelica Gallegos. Written for architects, designers, planners, developers, city councilmembers,and engineers, this book encourages all composers of the built environment to envision alternative futures and purposefully respond.
Keywords: ARCHITECTURE / General; ARCHITECTURE / Criticism; ARCHITECTURE / Design & Drafting; Architectural design; Forecasting; Planning